Peran Core Self Evaluation dalam Memprediksi Persipan Pensiun - Arini Widyowati; Noor Rochman Hadjam (HUMANITAS: Indonesian Psychological Journal, 2014)
ABSTRACTThis study examines the role of core self evaluation on predicting retirement preparation of preÂ retirement employees. This research involves 50 pre retirement employee of the exploration sectionÂ of â€œ X Companyâ€ who get pre retirement program on 2013. Retirement preparation scale is used toÂ measure effort of the employeeâ€™s retirement planning and core self evaluation is measured throughÂ core evaluation scale. Results show that there is no significant effect of core self evaluation onÂ retirement preparation (F = 0.581, p = 0.679, p > 0.05). Based on data analysis it indicated thatÂ core self evaluation does not have effect on retirement preparation. Itâ€™s mean that core self evaluationÂ could not predict employeeâ€™s retirement preparation. Thera are non-motivational and cultural factorsÂ that affect employeesâ€™ intention on retirement preparation.Keywords: core self evaluation, emotional stability, self esteem, self efficacy, locus of control,Â retirement preparation